Pemanfaatan Raspberry Pi untuk Sistem Penghitung Mobil Otomatis pada Kampus UKDW - Kristian Adi Nugraha; Laurentius Kuncoro Probo Saputra (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
The number of vehicle keep increasing over time, causing some problems such as traffic jam and requirement of extra parking space. Universitas Kristen Duta Wacana (UKDW) is an university that has similar problem, lack of parking space at certain hours. That won't be a problem if campus activities such as course, student activities, etc. can spread evenly at all hours, not focused at one time only. But determine the accurate schedule is a difficult task, because it requires someone who observes all vehicles entering and exiting campus area all over time. This research propose a solution to create automatic system that can count all vehicles (car) that entering and exiting campus area, then the data can be used as a consideration in determining the scheduling at the next time, the lack of parking space area can be avoided. The system was built with internet of things technology using Raspberry Pi and camera as the main component with main server at the backend to store the data. That system is also using background substraction algorithm for counting Â the number of vehicles that entering and exiting campus area. The accuracy of the system at counting vehicles is 70%.